The Sperrgebiet Domain, Aurus Mountains, SW Namibia: A ~2020–850 Ma window within the Pan-African Gariep Orogen - Thomas, R.; Macey, P.; Spencer, Christopher; Dhansay, T.; Diener, J.; Lambert, C.; Frei, D.; Nguno, A. (Elsevier BV, 2016)
© 2016 Elsevier B.V. The Aurus Mountains in SW Namibia form a tectonic inlier (Sperrgebiet Domain) within the Neoproterozoic Gariep belt. We document the geological history from field mapping, whole-rock geochemical, metamorphic and U-Pb zircon isotope data. The calc-alkaline granodioritic orthogneisses of the Wasserkuppe Suite, dated at ~2020 Ma, are the predominant, oldest rocks, which are interpreted to form part of a ~2 Ga “Sperrgebiet arc”; the tectono-magmatic equivalent of the ~250 km wide Richtersveld arc to the southeast, but ~100 Ma older. ~2 Ga detritus is common throughout the western Namaqua belt, but its source was hitherto unknown. The suite intruded synchronously with amphibolite facies metamorphism and deformation, considered an early phase of the Palaeoproterozoic Orange River Orogeny. The Wasserkuppe Suite is intruded by alkali granite and microgranodiorite dated at ~1885 Ma, interpreted as equivalents of the Vioolsdrif Suite (Richtersveld arc). The Sperrgebiet Domain is thus seen as an early phase of a process of Palaeoproterozoic island-arc development at the margins of the Archaean Kaapvaal Craton/Rehoboth Province. It was cannibalised by the later Richtersveld arc which dominated the palaeogeography of this part of southern Africa 100 m.y. later, and which forms the crustal infrastructure of much of Western Namaqualand. The Palaeoproterozoic arc rocks are overlain by a clastic metasedimentary sequence; the Aurus Schist. Detrital zircon geochronology indicates that these rocks were predominantly derived from both arcs, with minor Archean and younger ~1800 Ma detritus, of unknown source(s). Bodies of latest Mesoproterozoic (~1000 Ma) Warmbad Granite and pegmatite are mapped throughout the area and represent the only Namaquan rocks definitively identified. Evidence for Namaquan metamorphic or tectonic imprints are lacking, apart from a garnet-clinopyroxene metabasic inclusion in a quartz-feldspar leucogneiss which gave a typical “Namaquan” P-T estimate of ~700–750 °C at 6–7 kbar. The leucogneisses, distributed throughout the area, were dated at ~840 Ma and are interpreted as metamorphosed felsic igneous rocks of the Richtersveld Suite, formed during early rifting of the proto-Gariep basin. The Sperrgebiet rocks are variably deformed by the Pan-African Gariep Orogeny that produced regionally-pervasive fabrics, predominantly partitioned into discrete high-strain shear zones in a NW-trending sinistral transpressive tectonic regime.